Climate change and temporal-spatial variation of tropical storm-related Natechs in the United States from 1990 to 2017: Is there a link?. (August 2021) - Luo, Xiaolong; Cruz, Ana Maria; Tzioutzios, Dimitrios
Abstract: Natural hazard triggered hazardous materials (hazmat)-release accidents, known as Natechs, can cause extensive damage and losses. Several studies found that tropical storms are becoming an important cause of Natechs. Understanding whether and how climate change affects the incidence of tropical storms-related Natechs becomes a crucial issue for industrial risk management and adaptation to climate change. This study analyzed the temporal-spatial variation of tropical storms-related Natech incidence on the eastern side of the United States (US) from 1990 to 2017 based on the analysis of hazmat-release accidents reported to the US National Response Center. The results show that the frequency and density of tropical storms-related Natechs are on the rise. In order to explore the cause of such changes, this study investigates the relationships between the temporal-spatial variation of the incidence of tropical storms-related Natechs, and the accumulated cyclone energy, the North Atlantic Oscillation (NAO) index and the Oceanic Niño Index (ONI), and other variables. The results suggest an indirect link between climate change and the temporal-spatial variation of the incidence of related Natechs due to its effect on tropical storm activity. The presented evidence suggests that, when developing Natech risk management plans, the potential effects of climate change should be considered. Not only facilities' owners/operators, but government, first responders and other stakeholders should consider how climate change will affect the Natech risk landscape, and implement more effective regulations to manage Natech risk in wider areas.